FEATURES OF CONTEMPORARY CHINESE STYLE IN DIGITAL FASHION DESIGN: CASES OF FASHION INDUSTRY PRODUCTS - WU, S.; YEZHOVA, O. V. (Art and Design, 2023)
To analyze the artistic and aesthetic characteristics that influence the modern digital design of Chinese-style clothing, the practice of creation and to propose modern digital design solutions in the design of jewelry, style and clothing. The theoretical and practical research methods have been used: analysis of scientific and professional literature on the topic of research, design based on the evolution of patterns and forms, analysis of analogs of design objects, design and creation of a product using specialized software. The main features of modern Chinese style in clothing design and personal image are revealed. The main characteristics of the design style solutions of modern Chinese digital clothing and personal image are summarized. According to the results of the research, projects of digital design of jewelry and personal image were developed. The characteristics of the main forms of digital fashion design in the Chinese style are analyzed, the development trends that affect modern Chinese fashion design are revealed, and some practical results of digital fashion design are summarized. The results of the study can be used to analyze and develop industrial and consumer-oriented design of clothing, jewelry and personal image in Chinese style. The results of the study can be used to further explore digital clothing design and personal image in Chinese style for media content.